1989
DOI: 10.1055/s-2006-962104
|View full text |Cite
|
Sign up to set email alerts
|

Chemotypic Variation in Indian Spearmint*

Abstract: Because of their valuable essential oil, several species of Mentha (Lamiaceae) have been introduced into vailous countries for their commercial cultivation. The occurrence of about six Mentha species has been recorded in India (1). During the last decade, efforts have been made by our institute to develop improved agrotechnology and genetically better strains for the commercial cultivation of various Mentha species (2, 3). In continuation of this project and our programme of screening new Indian essential oils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…The Bray-Curtius percentage, selected as a measure of similarity and simple average, was used as the basis of cluster analysis. Earlier, on the basis of chemotaxonomic studies, M. spicata has been classified into carvone [6], piperetenone oxide [16], linalool [17], menthone/isomenthone [18], dihydrocarvone [19] and menthyl acetate types [20], but in the present study we could find only the carvone and piperetenone oxide types, along with two mixed populations (collections I and II), which contain both carvone and piperetenone oxide as the major compounds. This may be possible due to the hybrid nature of the plant.…”
contrasting
confidence: 53%
“…The Bray-Curtius percentage, selected as a measure of similarity and simple average, was used as the basis of cluster analysis. Earlier, on the basis of chemotaxonomic studies, M. spicata has been classified into carvone [6], piperetenone oxide [16], linalool [17], menthone/isomenthone [18], dihydrocarvone [19] and menthyl acetate types [20], but in the present study we could find only the carvone and piperetenone oxide types, along with two mixed populations (collections I and II), which contain both carvone and piperetenone oxide as the major compounds. This may be possible due to the hybrid nature of the plant.…”
contrasting
confidence: 53%
“…The effects of nitrogen and phosphorus doses on all traits of spearmint genotypes were found to be significant (P < 0.01). Current findings comply with the findings of earlier studies indicating the effects of years, cultivars, ecology, fertilization, irrigation, harvest period, and genetic factors on spearmint essential oil composition (Misra et al, 1989;Özgüven and Kırıcı, 1999;Kirakosyan et al, 2004;Zobayed et al, 2005;Gopichand et al, 2013). The 1.8-cineole, 4-terpineol, and pulegone contents were higher in the second year than in the first year and such findings comply with the results of Kirakosyan et al (2004), proposing that cold weather or water stress might have increased polyphenolic compound contents.…”
Section: Resultssupporting
confidence: 91%
“…Although organoleptic evaluation of the oil of mutant 643 had suggested an abnormal composition, the analytical results were nevertheless surprising in that over 85% of the oil was composed of C3-oxygenated monoterpenes (Table I), of which well over half were 3-keto-1,2-oxides ( Fig. 1 M. cordifolia chemotypes (10,18), but the presence of these compounds and their C3-oxygenated congeners in spearmint types is unusual (17,22). A developmental study of oil compositional change as a function of leaf maturity of plants grown under controlled conditions indicated that the expansion of Scotch spearmint leaves from 0.5 cm to over 5 cm was accompanied by a gradual decrease in limonene content from over 20% to about 15%, with a gradual increase in carvone content from 50% to about 70%.…”
Section: Essential Oil Analysismentioning
confidence: 99%